Experimental Performance Evaluation of a MR Brake-Based Haptic System for Teleoperation - Gang, Han Gyeol; Choi, Seung-Bok; Sohn, Jung Woo (Frontiers in Materials, 2019)
In this work, a new type of haptic system inspired by human wrist motion is proposed, and its performance is evaluated experimentally for teleoperation. The master device has 3-DOF rotational motion, which is the same as human wrist motion; semi-active magnetorheological brakes are installed to generate a haptic effect for the operator. To achieve a good haptic feedback effect, the master device is designed with a lightweight structure and the haptic actuator is designed with minimal size. The slave robot has 3-DOF rotational motion using servomotors, a five-bar linkage mechanism, and a pivot point. In the proposed slave robot, instead of a commercial torque sensor, a newly designed torque sensor that uses three force sensors is adopted. It is experimentally validated that the proposed haptic system has good performance in terms of the tracking control of the desired position and repulsive torque. In addition, to ensure that the human operator can actually distinguish the different magnitudes of torque, a simple recognition test is carried out. Although not continuous, it is confirmed that the torque difference can be distinguished at three levels. Finally, it is demonstrated that the proposed haptic system can be effectively applied to a real teleoperation system.